2007
DOI: 10.3892/or.17.5.1027
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to CPT-11 and platinum derivatives of stage III/Dukes' C colorectal cancer with occult neoplastic cells in lymph node sinuses

Abstract: The sensitivity of LN metastases to anticancer drugs such as CPT-11 and platinum agents was investigated by assessing Topo-1 and Bax/ERCC-1 expression in patients who had stage III/Dukes' C colorectal cancer with ONCs. In the recurrence group (RG) (n=21), immunohistochemical expression of Topo-1 was high in 8 patients (38.1%), and low in 13 patients (61.9%), while the non-recurrence group (N-RG) (n=12) showed high expression in 1 patient (8.3%) and low expression in 11 patients (91.7%) (not significant; N.S.).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…According to some reports, addition of CPT-11 or L-OHP to 5-FU/LV therapy has nearly equivalent of anticancer drug sensitivity. In the first-line setting following curative resection, CPT-11 is a more reasonable choice than L-OHP because of a low incidence of neurological adverse events such as neuropathy and paresthesia and because it is less costly (11,12,20). It would seem advisable to retain L-OHP as a second-line treatment for distant metastasis/recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some reports, addition of CPT-11 or L-OHP to 5-FU/LV therapy has nearly equivalent of anticancer drug sensitivity. In the first-line setting following curative resection, CPT-11 is a more reasonable choice than L-OHP because of a low incidence of neurological adverse events such as neuropathy and paresthesia and because it is less costly (11,12,20). It would seem advisable to retain L-OHP as a second-line treatment for distant metastasis/recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the importance of postoperative adjuvant chemotherapy presumably lies in achieving the eradication of residual free cancer cells, which circulate around the body in the perioperative period (10)(11)(12) (10)(11)(12). Although the dosage and administration regimen also have an important influence on the activity of drugs, the most important factor is tumor sensitivity and the activity of any additional drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of tumor sensitivity to 5-FU/LV therapy at the time of systemic dispersion of circulating ONC clusters that may develop into metastases has revealed that few tumors show a high sensitivity represented by a high-TS/low-DPD level, suggesting that this regimen might be too weak (39,40). To increase the potency of this regimen, addition of CPT-11 or L-OHP which are more popular in the West than in Japan could be effective with respect to interactions and potentiation by modulation (14 -16).…”
Section: Discussionmentioning
confidence: 99%
“…In patients who were not indicated for surgery, anticancer agents other than those mentioned above were administered as second-line treatment. Radiotherapy was added in the case of rectal cancer for the local recurrence involving the pelvic floor (12)(13)(14). As a general rule, outpatient follow-up included measurement of tumor markers 3-4 times per year and ultrasonography/computed tomography (US/CT) 3-4 times a year, with recurrence/metastasis being confirmed by both US and CT (10,13).…”
Section: Methodsmentioning
confidence: 99%
“…In general, Stage II patients received postoperative adjuvant chemotherapy with oral UFT/PSK (Krestin) for 12 months or longer (8)(9)(10). Stage III patients received intravenous 5FU/LV or 5FU/LV in combination with CPT-11 for 6 months after surgery, and then received oral UFT/Uzel (an oral calcium folinate) or UFT/PSK for 12 months or longer (11)(12)(13). In principle, surgical resection was chosen as the first-line treatment for postoperative recurrence/metastasis.…”
Section: Methodsmentioning
confidence: 99%